Undetectable Free Aromatic Amino Acids in Nails of Breast Carcinoma: Biomarker Discovery by a Novel Metabolite Purification VTGE System - Mitruka, Manmohan; Gore, Charusheela R.; Kumar, Ajay; Sarode, Sachin C.; Sharma, Nilesh Kumar (Frontiers in Oncology, 2020)
BACKGROUND: Metabolic reprogramming in breast cancer is depicted as a crucial change in the tumor microenvironment. Besides the molecular understanding of metabolic heterogeneity, appreciable attentions are drawn to characterize metabolite profiles in tumor tissue and derived biological fluids and tissue materials. Several findings reported on the metabolic alterations of free aromatic amino acids (FAAAs) and other metabolites in biological fluids. Furthermore, there is a significant gap in the development of a suitable method for the purification and analysis of metabolite biomarkers in nails of cancer patients. METHODS: To address the metabolite alterations specifically FAAAs level in nails, fingernail clippings of breast cancer patients (N=10), and healthy subjects (N-12) were used for extraction and purification of metabolites. Here, we report a novel and specifically designed vertical tube gel electrophoresis (VTGE) system that helped for the purification of metabolites in the range of (100-1000 Da) from nail materials. The claimed VTGE system uses 15% polyacrylamide under non-denaturing and non-reducing conditions that makes eluted metabolites directly compatible with LC-HRMS and other analytical techniques. Qualitative and quantitative determination of FAAAs in nail lysates were done by positive ESI mode of Agilent LC-HRMS platform. RESULTS: The analysis on collected data of nail metabolites clearly suggests that FAAAs including tryptophan, tyrosine, phenylalanine and histidine are undetectable in nail lysates of breast cancer over healthy subjects. This is a first report that shows the highly reduced levels of FAAAs in nails of breast cancer. Furthermore, present observation is in consonance with previous findings that support that breast cancer patients show cancer cachexia, high amino acid catabolism that drive metabolite driven cancer growth and proliferation. CONCLUSION: This paper provides a proof of concept for a novel and specifically developed VTGE process that assisted to show the first evidence on undetectable level of FAAAs in nails of breast cancer patients as metabolite biomarkers. Here, the authors propose the potential use of VTGE assisted process to achieve metabolomic discovery in nails of breast cancer and other tumor types.